2022
DOI: 10.3390/app12063023
|View full text |Cite
|
Sign up to set email alerts
|

Authentication and Authorization in Microservices Architecture: A Systematic Literature Review

Abstract: The microservice architectural style splits an application into small services, which are implemented independently, with their own deployment unit. This architecture can bring benefits, nevertheless, it also poses challenges, especially about security aspects. In this case, there are several microservices within a single system, it represents an increase in the exposure of the safety surface, unlike the monolithic style, there are several applications running independently and must be secured individually. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Almeida et al. [ 8 ] prompted a systematic literature review to address issues pertaining to the difficulties, strategies, and tools for handling authentication and authorization in microservices. Although they focused explicitly on authentication and authorization, their studies vastly related to security mechanisms and the open-source tools and approaches related to that.…”
Section: Related Workmentioning
confidence: 99%
“…Almeida et al. [ 8 ] prompted a systematic literature review to address issues pertaining to the difficulties, strategies, and tools for handling authentication and authorization in microservices. Although they focused explicitly on authentication and authorization, their studies vastly related to security mechanisms and the open-source tools and approaches related to that.…”
Section: Related Workmentioning
confidence: 99%
“…A comprehensive literature review was performed by Almeida et al. [ 16 ] focusing on the issues, solutions, and tools related to authentication and authorization in microservices. They identified that the literature concentrated on identifying the open-source solutions of the specifications.…”
Section: Related Workmentioning
confidence: 99%
“…For the client and the user, authentication and authorization serve slightly different purposes [ 6 ]. The purpose of the application system in the case of a user is to verify his or her identity and grant him or her access to the relevant resources and functions.…”
Section: Introductionmentioning
confidence: 99%